Efficacy of repetitive transcranial magnetic stimulation for post-stroke depression: a systematic review and meta-analysis of randomized clinical trials - Shao,D. (2021)
We aimed to conduct a meta-analysis to evaluate the efficacy of repetitive transcranial magnetic stimulation (rTMS) in patients with post-stroke depression (PSD). Six relevant electronic databases (PubMed, CENTRAL, Embase, Web of Science, CINAHL, and PsycINFO) were searched. Randomized controlled trials (RCTs) that compared rTMS with control condition for PSD were included. The mean change in depression symptom scores was defined as the primary efficacy outcome. Secondary outcomes included the remission rate of depression, stroke recovery, and cognitive function recovery. In total, 7 RCTs with 351 participants were included. At post-treatment, rTMS was significantly more effective than the control condition, with a standardized mean difference (SMD) of -1.15 (95%CI: -1.62 to -0.69; P<0.001, I2=71%) and remission with an odds ratio (OR) of 3.46 (95%CI: 1.68 to 7.12; P<0.001; I2=11%). As for stroke recovery, rTMS was also better than the control condition (SMD=-0.67, 95%CI: -1.02 to -0.32; P<0.001). However, no significant difference was found for cognitive function recovery between the two groups (SMD=4.07, 95%CI: -1.41 to 9.55; P=0.15). To explore the potential moderators for the primary outcome, a series of subgroup and sensitivity analyses were performed. The results implied that rTMS may be more effective in Asian samples than in North American samples (P=0.03). In conclusion, from the current evidence in this study, rTMS could be an effective treatment for patients with PSD. Further clinical studies with larger sample sizes and clearer subgroup definitions are needed to confirm these outcomes.